Cadre législatif québécois pour la protection des espèces sauvages en situation précaire: évaluation critique et recommandations pour une révision majeure - Fanie Pelletier; Pierre Dumont; Joanie Van de Walle; Daniel Jauvin; David Rodrigue (Canadian Science Publishing, 2024)
In Quebec, the Act Respecting Threatened or Vulnerable species (ARTV), adopted in 1989, aims to safeguard Quebec's wild genetic diversity by protecting species at risk. However, since its implementation about 30 years ago, it has been repeatedly pointed out that the application of the Quebec legislative framework for the protection of wildlife species at risk was often slow and inadequate. The aim of this article is therefore to make a series of observations on the limits of current legislation and then propose nine urgent recommendations to improve the effectiveness of conservation efforts for species at risk in Quebec. Our recommendations aim to increase the efficiency and transparency of the designation process, reconsider compensation mechanisms for the loss of critical habitat, and harmonize species status between the federal and provincial levels. We hope that our article will pave the way for a constructive discussion leading to an improved protection of wildlife species in precarious situations and their persistence for future generations. The English version of this article is available in the Supplementary material file.